Effects of impulsive and reflective cognitive styles on metacognitive thinking and deep understanding of religious concepts - Awadh Ali Yahya Al-Qahtani; Naif Adeeb Al-Otaibi (Acta Psychologica)
This endeavor explores the impact of the diversity of cognitive styles on metacognitive thinking and a deep understanding (DU) of religious concepts. It ascertains the relationship between the DU of such concepts and metacognitive thinking skills among secondary school students. For this purpose, a correlational research design was adopted, and data were collected from 118 learners selected from a secondary school in Saudi Arabia. The participants were divided into two groups: reflective cognitive style learners and impulsive cognitive style learners. Both groups were tested for their reflective-impulsive cognitive styles, religious conceptual knowledge, and metacognitive thinking skills. Results showed statistically significant differences between the mean scores of the two groups regarding their DU of religious concepts. The differences leaned toward the reflective group. Also, statistically significant differences existed between the mean scores of the two groups in metacognitive thinking skills, and the differences leaned toward the reflective group. Moreover, a positive significant relationship between metacognitive thinking skills and DU of religious concepts was evident among the reflective group and non-significant among the impulsive group. The results suggest that reflective learners are more understanding of religious concepts and use metacognitive thinking skills more than their impulsive learners. The findings support fostering DU and metacognitive thinking skills, especially among impulsive students, to orient students toward rational problem-solving and decision-making approaches.